From the École polytechnique to the École de la régulation - Yamina Tadjeddine (Revue de la Régulation)
This article traces the intellectual career of Michel Aglietta, an economist attached to the École de la regulation (Regulation school), from his youth to the publication of his book Régulation et Crise du capitalisme (1976). It is one of a series of recent studies on the structuring of economic thought, and macro-economic theory in particular, at the turn of the 1970s. The theoretical perspective of the article combines the history of economic thought and the sociology of science to place Aglietta’s career in a dual dynamic: the course of a lifetime–education, places of work, scientific collaborations–and the economic, social and political contexts he has traversed. The study of published articles is supplemented by recourse to archives and interviews with Aglietta and those who worked with him. The structure of the article follows the three institutions that Aglietta frequented and that shaped him as a student at the École Polytechnique (1959–1965), a senior civil servant at the Institut national de la statistique et des études économiques (INSEE) (1965–1970) and a doctoral student at the Sorbonne under the supervision of Raymond Barre (1970–1974). The presentation of Aglietta’s life and career between 1959 and 1976 helps to explain his contribution to the advent of Regulation theory, and also to understand his stance as an expert economist in the service of public policy.